The risks associated with wastewater reuse and xenobiotics in the agroecological environment - Fatta-Kassinos, Despo; Kalavrouziotis, Ioannis K.; Koukoulakis, Pródromos H.; Vasquez Christodoulou, Marlen (My University, 2011)
Treated wastewater reuse for irrigation, landscape and surface or groundwater replenishment purposes is being widely implemented. Although the reuse practice is accompanied by a number of benefits relating to the enhancement of water balances and soil nutrition by the nutrients existing in the treated effluents, a number of unanswered questions are still related to this practice. Besides the lack of knowledge in respect to possible elemental interactions that may influence the accumulation of heavy metals and other elements in the soil and the subsequent uptake by plants and crops, during the last several years, the technological progress in respect to analytical chromatographic methods has enabled the identification and quantitation of a number of organic xenobiotic compounds in treated wastewater. Therefore it is now known that the effluents' remaining organic matter most usually expressed as Chemical Oxygen Demand consists of a number of biorecalcitrant organic xenobiotic compounds including potential endocrine disrupting compounds (EDCs), pharmaceuticals, etc. It is also widely accepted that the currently applied treatment processes for urban wastewater abatement fail to completely remove such contaminants and this lead to their subsequent release in the terrestrial and aquatic environment through disposal and reuse applications. The number of studies focusing on the analysis and the toxicological assessment of such compounds in the environment is constantly increasing the aim being to bridge the various knowledge gaps associated with these issues. The existing knowledge in respect to the relevant existing legislation framework, the types of elements and chemicals of concern, the uptake of xenobiotic pollutants and also that of other neglected chemical elements along with their potential environmental interactions constitute the focus of the present review paper. The review addresses the problems that might be related to the repeated treated wastewater release in the environment for reuse applications in respect to the wastewater residual load in heavy metals, accumulating in soil and plants and especially in their edible parts, in xenobiotic compounds, including EDCs, pharmaceuticals and personal care products, drugs' metabolites, illicit drugs, transformation products, and also genes resistant to antibiotics.
Keywords: Wastewater; Reuse; Irrigation; Xenobiotics; Antibiotic resistant bacteria; Heavy metals